2010
DOI: 10.1007/s00467-010-1478-1
|View full text |Cite
|
Sign up to set email alerts
|

Pneumatosis intestinalis in a child with nephrotic syndrome and norovirus gastroenteritis

Abstract: We report a child with idiopathic nephrotic syndrome whose condition was complicated by extensive pneumatosis intestinalis during a nephrotic relapse. The concomitant use of steroid and immunosuppressive agents and a preceding norovirus gastroenteritis infection were identified as risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…Pneumatosis intestinalis is another rare cause of abdominal pain in nephrotic patients, described in 3 adults and 1 child [31][32][33][34]. It is a condition characterized by the linear or cystic accumulation of gas within the gastrointestinal wall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pneumatosis intestinalis is another rare cause of abdominal pain in nephrotic patients, described in 3 adults and 1 child [31][32][33][34]. It is a condition characterized by the linear or cystic accumulation of gas within the gastrointestinal wall.…”
Section: Discussionmentioning
confidence: 99%
“…[20] Ete et al [21] Al-Mardini and Hddad [26] Kelly et al [15] Present case involvement. Gut edema, the use of immunosuppressive and preceding viral gastroenteritis are possible predisposing factors [31].…”
Section: Discussionmentioning
confidence: 99%
“…This virus is transmitted through the fecaleoral route and usually causes acute self-limiting gastrointestinal infections. Norovirus infection is also associated with many clinical symptoms, such as necrotizing enterocolitis, infantile epileptic encephalopathy, emphysema enteropathy, and sporadic intravascular coagulation (Chan et al, 2010; Centers for disease control and prevention 2002; Medici et al, 2010;Turcios-Ruiz et al, 2008). In developing countries, norovirus infection causes approximately 200,000 deaths of children fewer than 5 years old each year (Hall et al, 2013).…”
Section: Norovirusmentioning
confidence: 99%
“…Norovirus gastroenteritis has recently been identified as a significant cause of morbidity and mortality in the immunocompromised, and can result in long-term persistent disease (reviewed by Bok & Green, 2012). Norovirus infection has also been associated with a number of more significant clinical outcomes: necrotizing enterocolitis (Turcios-Ruiz et al , 2008), seizures in infants (Medici et al , 2010), encephalopathy (Ito et al , 2006), pneumatosis intestinalis (Chan et al , 2010; Kim et al , 2011) and disseminated intravascular coagulation (CDC, 2002), to name but a few. In developing countries, an estimated 200 000 deaths in children <5 years of age are thought to be due to norovirus infections (Patel et al , 2008) and they have recently been reported as the second leading cause of gastroenteritis-related deaths in the USA, typically resulting in 797 deaths per annum (Hall et al , 2013).…”
Section: Introductionmentioning
confidence: 99%